Genotyping of Mycobacterium tuberculosis using whole genome sequencing - Amlerova, Jana; Bitar, Ibrahim; Hrabak, Jaroslav (Folia microbiologica, 2018)
Tuberculosis (TB) is considered one of the most serious infectious diseases worldwide. Effective control of tuberculosis infection involves multiple steps, such as reliable detection, treatment, an epidemiological control as a part of case management, and further surveillance and monitoring of TB spread in the human population. Due to the accelerating advances in molecular biology, especially in DNA sequencing, in the past decade, the application of these methods has become crucial for TB evolution studies, differentiation of Mycobacterium tuberculosis genotypes, and their distribution. Currently, several molecular genetic methods are available. The oldest typing methods (e.g., IS6110-RFLP, spoligotyping, and MIRU-VNTR) can discover the chain of transmission to the patient. Currently, whole genome sequencing facilitates is furthermore able to identify the source of infection, the transmission trays among individuals sharing the same isolate, as well as determination of the TB evolution and its resistance to antituberculotic agents. It is obvious that this technique will become a new gold standard in genotyping methods in tuberculosis molecular epidemiological studies. In this article, molecular genetic typing methods with a special focus on whole genome sequencing and data management are reviewed.
Keywords: sekvenování celého genomu; molekulární epidemiologie; Molecular Typing; Genotype; Drug Resistance, Bacterial; Genome, Bacterial; Molecular Epidemiology; tuberkulóza; Tuberculosis; Phylogeography; genom bakteriální; lidé; Humans; bakteriální léková rezistence; fylogeografie; molekulární typizace; genotyp; Whole Genome Sequencing; Mycobacterium tuberculosis